Implementasi Teknologi QR Code Tokoh Pahlawan Dalam Kegiatan Belajar Mengajar Di SD Katolik Yohanes Gabriel Sidodadi, Blitar - Pramananditya, Benedicto Reinaldy; Wahyuningsih, Yulia; Hayong, Emanuel Amstrong; Gracitwo, Brielt Bella (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2024)
Technological advances in the modern era are now becoming a trend in the lives of every individual and in various fields. One of them is QR (Quick Response) Code technology in the Android-based Heroes application. This research explains the community service program, especially for partners at Yohanes Gabriel Catholic Elementary School located in Sidodadi, Garum District, Blitar Regency. Our service is by creating an application that contains sketches of the faces of Indonesian Heroes and their struggles both before and after independence, wrapped in short videos. The method used is face-to-face where we provide guidance to teachers in using the application we created and provide outreach to elementary school students regarding the application created. With this application which utilizes the latest technology, it has had a positive impact, especially for our partners at Yohanes Gabriel Catholic Elementary School, where the elementary school teachers can use the application we created in their teaching and learning activities..            Keywords: QR code; community service; android